Concise Human Physiology - Sukker, M. Y.; El- Mumshig H. A.; Ardawi- M. S. M. (Blackwel, 2000)
This textbook on human physiology, written for medical students, presents the main facts and concepts in a straightforward style. It is especially useful to those for whom English is a foreign language
Keywords: Human Physiology; Human Physiology -- Study and teaching -- Developing countries; Physiology -- View all subjects